Mendayung (Memanipulasi Wacana) di Antara Dua Karang: Discursive hedging Indonesia dalam Indo-Pasifik - Kevin Ali Sesarianto (Hasanuddin Journal of International Affairs, 2023)
In the Indo-Pacific constellation which targets political, security and economic issues, Indonesia is constructed as a middle power country. This construction originates from the political reality that Indonesia must hedge between the influence of the United States and China. In other words, the Indo-Pacific is a construction in which there are conflicting interests of the two great powers. Using the postcolonial critical discourse analysis method, this paper explores the construction that Indonesia is doing in ASEAN regarding the Indo-Pacific, namely the ASEAN Outlook on the Indo-Pacific. This paper looks at two important things: (1) the discursive power relations embodied in Indo-Pacific discourse and (2) the activity of manipulating discourse so that Indonesia is merely in a "safe" position in the conflict of big powers, and even tends to take advantage of it. As a result of these findings, this paper reconstructs the identity and role of Indonesia's middle power: Indonesia is not a bearer of inclusivity or an honest broker, but merely a client of two major powers. ? Dalam konstelasi Indo-Pasifik yang menyasar permasalahan politik, keamanan, dan ekonomi, Indonesia dikonstruksikan sebagai negara middle power. Konstruksi tersebut bersumber dari kenyataan politik bahwa Indonesia harus melakukan hedging di antara pengaruh Amerika Serikat dan Cina. Dengan kata lain, Indo-Pasifik adalah sebuah konstruksi yang terdapat pertentangan kepentingan dua great oiwer di dalamnya. Menggunakan metode analisis wacana kritis poskolonial, tulisan ini mendalami konstruksi yang Indonesia lakukan dalam ASEAN terkait Indo-Pasifik, yakni ASEAN Outlook on the Indo-Pacific. Tulisan ini melihat dua hal penting: (1) relasi kuasa diskursif yang terkandung dalam pewacanaan Indo-Pasifik dan (2) aktivitas manipulasi wacana agar Indonesia sekedar berposisi ?aman? dalam konflik kekuatan besar, bahkan cenderung memanfaatkan. Akibat temuan tersebut, tulisan ini merombak identitas dan peran middle power Indonesia: Indonesia bukan pembawa inklusivitas atau honest broker, tetapi sekedar klien dari dua kekuatan besar.